DEVELOPMENT OF ELECTRONIC TEXTBOOKS IN HELPNDOC SYSTEM - Alexander Yu. Stremnev (Высшее образование в России, 2016)
The article discusses the problems of methodological support in the modern educational process. The author substantiates the necessity of preparing by all the teachers of e-learning courses covering all aspects of academic disciplines, including both theoretical information and modules for elaboration. Provides a list of structural elements of such courses and provides an overview of the capabilities of one tool for their implementation. The review focuses on the effective use of the navigation system created in resources, search tools, interactive and multimedia content, and the simplicity of the user interface. The article pays attention to the most important details relating to the layout of e-courses: support for Cyrillic encodings, the import of content from text documents, a built-in editing and formatting tools, choosing the types of media files, integration of existing materials into courses. The paper emphasizes that the tools should be capable of creating high quality teaching resources by the authors with only basic knowledge in information technology.